1992
DOI: 10.1088/0029-5515/32/12/i04
|View full text |Cite
|
Sign up to set email alerts
|

Density fluctuations and spectral broadening during the lower hybrid current drive experiment on ASDEX

Abstract: The broadening of the injected radiofrequency (RF) line in the frequency spectra detected during the lower hybrid (LH) experiment in ASDEX is studied. The parametric decay instabilities (PDI) and the scattering due to density fluctuations are considered as possible causes of the broadening. The analysis of the parametric dispersion relation shows that parametric instabilities driven by ion sound quasi-modes have the highest growth rates, but their RF power threshold is higher than the RF power available in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
26
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 12 publications
6
26
0
Order By: Relevance
“…About 0.2 MHz (measured 10 dB below the power peak, by excluding the line width intrinsic to the RF sources, roughly a few tens kilohertz) was observed during typical LHCD experiments (operating with n e ≈ 1.1 × 10 19 m −3 , B T ≈ 3 T, I P ≈ 3 MA). Accordingly with the typical trend of pump broadening observed in different LHCD experiments [25,27,[34][35][36], the pump broadening of JET increased up to about 1 MHz when the operating plasma density in the bulk (and, correspondently, in the SOL) was a factor of two higher than in the case of figure 2.…”
Section: Pump Broadening and Scrape-off Layer Parameters In The Lowersupporting
confidence: 76%
See 1 more Smart Citation
“…About 0.2 MHz (measured 10 dB below the power peak, by excluding the line width intrinsic to the RF sources, roughly a few tens kilohertz) was observed during typical LHCD experiments (operating with n e ≈ 1.1 × 10 19 m −3 , B T ≈ 3 T, I P ≈ 3 MA). Accordingly with the typical trend of pump broadening observed in different LHCD experiments [25,27,[34][35][36], the pump broadening of JET increased up to about 1 MHz when the operating plasma density in the bulk (and, correspondently, in the SOL) was a factor of two higher than in the case of figure 2.…”
Section: Pump Broadening and Scrape-off Layer Parameters In The Lowersupporting
confidence: 76%
“…In this section a summary is given of the measurements of spectral broadening performed in LHCD experiments of JET by means of RF probes and by microwave reflectometry of the plasma edge. Similar measurements were performed on ASDEX, which found that the pump broadening exhibits a non-linear behaviour with the operating plasma density of the SOL and with the level of the coupled LH power [27]. Measurements of spectral broadening in the LHCD regime were also performed by RF probes on Alcator C [25], FT [31,34] and JET [36].…”
Section: Pump Broadening and Scrape-off Layer Parameters In The Lowermentioning
confidence: 76%
“…The typical parameters relevant to the PI-driven quasimode are: k ⊥ ≈ 10 -15 cm -1 , ω/2π ≈ 0.2 -1 MHz, consistently with the frequency broadening measured in the LH range by RF probes, and in the density fluctuation range by microwave reflectometry [27,11]. Such common behavior is determined by the circumstance that all the LHCD experiments meet similar operating conditions, in the operating frequencies and scrape-off parameters, which determine mainly the growth rates and the launcher coupling performance as well.…”
Section: Broadening Of the Antenna Spectrum In Lhcd Experiments By Thsupporting
confidence: 79%
“…2 with the spectrum launched by the antenna of the LHCD experiments of JET. The occurrence of the PI-induced spectral broad-ening is supported by measurements of radio-frequency probe signals and of density fluctuations at the edge by microwave reflectometry performed in LHCD experiments [11][12][13]22]. Further details of the PI-induced spectral broadening analysis are related in Ref.…”
mentioning
confidence: 75%